A comparison of positive vicarious learning and verbal information for reducing vicariously learned fear. Issue 6 (18th August 2018) - Reynolds, Gemma; Wasely, David; Dunne, Güler; Askew, Chris
ABSTRACT: Research with children has demonstrated that both positive vicarious learning (modelling) and positive verbal information can reduce children's acquired fear responses for a particular stimulus. However, this fear reduction appears to be more effective when the intervention pathway matches the initial fear learning pathway. That is, positive verbal information is a more effective intervention than positive modelling when fear is originally acquired via negative verbal information. Research has yet to explore whether fear reduction pathways are also important for fears acquired via vicarious learning. To test this, an experiment compared the effectiveness of positive verbal information and positive vicarious learning interventions for reducing vicariously acquired fears in children (7–9 years). Both vicarious and informational fear reduction interventions were found to be equally effective at reducing vicariously acquired fears, suggesting that acquisition and intervention pathways do not need to match for successful fear reduction. This has significant implications for parents and those working with children because it suggests that providing children with positive information or positive vicarious learning immediately after a negative modelling event may prevent more serious fears developing.